Digitization of Educational Processes in Higher Education - Mahkamov Madaminjon Komilovich; Usmonov Johongir Nishonboevich; Usmonova Mavludahon Soyibjon qizi (Periodica Journal, 2022)
This article discusses the introduction of digital technologies for the organization and management of educational processes in higher educational institutions. The effectiveness of the introduction of digital technologies in the management of educational processes in higher educational institutions is shown
Keywords: IT technologies; digital economy; digital technologies; education